Early childhood caries. Updated overview: Narrative Literature Review - Hernandez, Miguel (2025)
Objective: The purpose of this literature review is to gather updated information on diagnostic and therapeutic guidelines for early childhood caries. Material and methods: PubMed, Embase, Ovid, Cochrane Central and Google Scholar were searched for appropriate articles up to 5 years old (up to January 2018 inclusive). 229 studies were identified, including 13 clinical trials that discussed different treatment modalities for teeth affected by this disease. Conclusion: Early childhood caries is an increasingly common disease and is a condition that presents a unique set of clinical challenges for dental health professionals. This updated information recommends starting treatment as early as possible to eliminate the risk of increased cavitations because of early childhood dental caries and its consequences in these patients.